2017
DOI: 10.1002/slct.201700361
|View full text |Cite
|
Sign up to set email alerts
|

The Use of AOBH‐DEHP Molecular Probe to Characterize BHDC Reverse Micelles Interfaces. Insights on the Interfacial Water Structure

Abstract: This work presents the use of the molecular probe: 3,6-bis (dimethylamino) acridinium bis-(2-ethylhexyl) phosphate salt, AOBH-DEHP. This probe is used to gain insights into the properties of the benzene/benzyl-n-hexadecyldimethylammonium chloride (BHDC)/water reverse micelles (RMs) interfaces. The techniques employed were absorption and emission spectroscopy in addition to the steady-state and, time-resolved fluorescence emission. For BHDC RMs without water addition, AOBH-DEHP can be used to determine the crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Since the early ‘80s, the formation of micelles in ILs took on relevance. Studies have been reported about these types of liquids used as a dispersing phase in micellar systems, , such as a polar solvent confined in reverse micelles. , In some studies, PILs are implemented as molecular probes to monitor reverse micelles. ,, Despite the versatility of these newly designed solvents, the greater limitation that ILs can have is the poor solubility of many solutes. Given this situation, it can be overcome by adding conventional cosolvents, taking into account that such an addition will tune the properties of the ILs as solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early ‘80s, the formation of micelles in ILs took on relevance. Studies have been reported about these types of liquids used as a dispersing phase in micellar systems, , such as a polar solvent confined in reverse micelles. , In some studies, PILs are implemented as molecular probes to monitor reverse micelles. ,, Despite the versatility of these newly designed solvents, the greater limitation that ILs can have is the poor solubility of many solutes. Given this situation, it can be overcome by adding conventional cosolvents, taking into account that such an addition will tune the properties of the ILs as solvents.…”
Section: Introductionmentioning
confidence: 99%
“…18,26−29 studies, PILs are implemented as molecular probes to monitor reverse micelles. 19,30,31 Despite the versatility of these newly designed solvents, the greater limitation that ILs can have is the poor solubility of many solutes. Given this situation, it can be overcome by adding conventional cosolvents, taking into account that such an addition will tune the properties of the ILs as solvents.…”
Section: ■ Introductionmentioning
confidence: 99%